Nitrogen-doped graphene-like carbon nanosheets from commercial glue: morphology, phase evolution and Li-ion battery performance. Issue 35 (18th July 2018) - Damodar, D.; Kumar, S. Krishna; Martha, S. K.; Deshpande, A. S.
Abstract : The morphology of nitrogen-doped graphene-like carbon nanosheets along with a proposed mechanism for ladder structure formation during carbonization of commercial glue. Abstract : We report a two-step process to synthesize nitrogen-doped graphene-like carbon nanosheets (N-CNS), using commercially available ethyl cyanoacrylate based super glue as a carbon precursor. In this process, super glue is polymerized in aqueous NaCl solution, followed by carbonization at 1000 °C. Scanning electron microscopy (SEM) and high resolution transmission electron microscopy (HRTEM) studies show that the resultant material consists of micron-sized carbon nanosheets with a wrinkled morphology. HRTEM, X-ray diffraction (XRD), XPS and Raman spectroscopic studies confirm the formation of nanocrystalline and graphitic, nitrogen-doped carbon nanosheets. A detailed FTIR analysis of the degradation products of the polymeric precursor (polyethyl cyanoacrylate) at various heat treatment temperatures under an inert atmosphere reveals that the polymer undergoes a cyclization process similar to polyacrylonitrile (PAN) during carbonization to yield the N-CNS. The N-CNS used as an anode for a lithium-ion battery shows stable reversible capacities of 480 mA h g −1 for 100 cycles, which indicates that N-CNS are promising materials for lithium-ion battery applications. In a broader perspective, a unique chemical transformation of polyethyl cyanoacrylate to graphitic carbon may be useful to design new nanostructured carbons for a plethora of applications.